The effect of hypothyroidism on the risk of diabetes and its microvascular complications: a Mendelian randomization study - Fang, Ting; Deng, Xiaoqing; Wang, Jingyi; Han, Fei; Liu, Xiangyang; Liu, Yajin; Sun, Bei; Chen, Liming (Frontiers in Endocrinology, 2023)
Context: Several observational studies have found that hypothyroidism is associated with diabetes and its microvascular complications. However, the cause and effect have not been clarified. Objective: The aim of the study was to examine the causality of such associations by a Mendelian randomization study. Methods: Two-sample Mendelian randomization analysis was conducted to investigate the associations. Summary statistics for hypothyroidism were from the UK Biobank, and diabetes and its microvascular complications were from the largest available genome-wide association studies. MR-Egger, weighted median, inverse variance weighted, simple mode and weighted mode were used to examine the causal associations, and several sensitivity analyses were used to assess pleiotropy. Results: Inverse variance weighted estimates suggested that hypothyroidism was associated with type 1 diabetes and type 1 diabetes with renal complications (β= 9.059926, se= 1.762903, P = 2.76E-07 and β= 10.18375, se= 2.021879, P = 4.73E-07, respectively) but not type 2 diabetes and type 2 diabetes with renal complications. In addition, hypothyroidism was positively associated with severe nonproliferative diabetic retinopathy and proliferative diabetic retinopathy (β= 8.427943, se= 2.142493, P = 8.36E-05 and β= 3.100939, se= 0.74956, P=3.52E-05, respectively).The study identified the causal roles of hypothyroidism in diabetes and its microvascular complications. Hypothyroidism can lead to type 1 diabetes, type 1 diabetes with renal complications, severe nonproliferative diabetic retinopathy and proliferative diabetic retinopathy.